2010
DOI: 10.1007/s00424-010-0804-6
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyeicosatrienoic acids and endothelium-dependent responses

Abstract: Epoxyeicosatrienoic acids (EETs) are cytochrome P450 metabolites of arachidonic acid that are produced by the vascular endothelium in response to agonists such as bradykinin and acetylcholine or physical stimuli such as shear stress or cyclic stretch. In the vasculature, the EETs have biological actions that are involved in the regulation of vascular tone, hemostasis and inflammation. In pre-constricted arteries in vitro, EETs activate calcium-activated potassium channels on vascular smooth muscle and the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
234
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(247 citation statements)
references
References 112 publications
11
234
0
2
Order By: Relevance
“…S4). Given that CYP enzymes are involved in the generation of endotheliumderived hyperpolarizing factor, which contributes to the shear stress-induced endothelium-dependent vasodilation (38,39), it will be important to elucidate the important role of LSS-activated PXR in the production of endothelium-derived hyperpolarizing factor. Nevertheless, physiological significance of flow-activated PXR awaits further investigation with the use of animal models with an EC-specific PXR overexpression or knockout approach.…”
Section: Discussionmentioning
confidence: 99%
“…S4). Given that CYP enzymes are involved in the generation of endotheliumderived hyperpolarizing factor, which contributes to the shear stress-induced endothelium-dependent vasodilation (38,39), it will be important to elucidate the important role of LSS-activated PXR in the production of endothelium-derived hyperpolarizing factor. Nevertheless, physiological significance of flow-activated PXR awaits further investigation with the use of animal models with an EC-specific PXR overexpression or knockout approach.…”
Section: Discussionmentioning
confidence: 99%
“…Four regioisomeric EETs (14,15-, 11,12-, 8,9-and 5,6-EETs) are synthesized by cytochrome P450. In the vasculature, EETs are synthesized by the endothelium with 14,15-and 11,12-EET representing the predominant isomers (3,4). The EETs have actions on both endothelial cells (ECs) and smooth muscle cells (SMCs) (5).…”
mentioning
confidence: 99%
“…Therefore, this effect leads to reduced Ca 2+ influx through voltage‐dependent calcium channel (VDCCs), decrease in [Ca 2+ ] i and subsequent vasorelaxation. Another possible mechanism by which EETs activate TRPV4 receptor was provided by Campbell and Fleming 42. They concluded that EETs act on cells of the endothelium to enhance the influx of Ca 2+ by TRPV4.…”
Section: Discussionmentioning
confidence: 99%